TINJAUAN KETERAMPILAN BANTINGAN PADA ATLET GULAT KABUPATEN BUNGO - DEKA ISMI MORI SAPUTRA; JHONY HHENDRA (Jurnal Muara Olahraga, 2020)
This research is motivated by the lack of kickback skills in Bungo District Wrestling Athletes. The purpose of this research is to determine the level of slamming ability of Bungo District Wrestling Athletes. This research is descriptive. This research was carried out at the Bungo District Wrestling Athletes Training Center. The population in this study is the Bungo District Gulat Athlete with a total of 33 people. The sample in this study were 6 athletes who actively participated in the exercise. Analysis techniques Data analysis used in this study uses quantitative descriptive statistics with percentages. The results showed that the level of slamming skills of Bungat Regency Wrestling Athletes was not entirely good. Based on the results of interviews with Trainers it is known that the maximum assessment for kickback skills is 25, while the acquisition of athlete scores indicates that athletes have scored 16, 17 and 18. These conditions are due to 1) Athletes have not been able to make falling movements properly, 2) Athletes have not been able to make a move out of the opponent's key when positioned below, 3) Athletes have not been able to catch their feet properly, 4) Athletes have not been able to do slamming opponents, 5) Athletes have not been fully able to infiltrate opponents, and 6) Athletes have not been fully able to do interesting movements of the opponent.